2021
DOI: 10.3389/fbioe.2021.734688
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and its Derivatives for Bone Tissue Engineering: In Vitro and In Vivo Evaluation of Graphene-Based Scaffolds, Membranes and Coatings

Abstract: Bone regeneration or replacement has been proved to be one of the most effective methods available for the treatment of bone defects caused by different musculoskeletal disorders. However, the great contradiction between the large demand for clinical therapies and the insufficiency and deficiency of natural bone grafts has led to an urgent need for the development of synthetic bone graft substitutes. Bone tissue engineering has shown great potential in the construction of desired bone grafts, despite the many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 149 publications
1
30
0
Order By: Relevance
“…Osteogenic differentiation is accelerated on graphene nanocomposite scaffolds due to the ability of graphene nanomaterials to the increase preconcentration of osteogenic inducer factors (β‐glycerophosphate and dexamethasone) via π – π stacking among the aromatic rings in the graphene and the biomolecules 115,174 . Additionally, graphene derivatives increase osseointegration and osteoconductivity by stimulating cellular osteogenic differentiation, as well as bone‐like apatite production and biomineralization on the surface of implants 110,175 . One of the main factors for mimicking the properties of articular cartilage superficial and deep zones is the lubrication feature that maintains low coefficients of friction of joints.…”
Section: Discussionmentioning
confidence: 99%
“…Osteogenic differentiation is accelerated on graphene nanocomposite scaffolds due to the ability of graphene nanomaterials to the increase preconcentration of osteogenic inducer factors (β‐glycerophosphate and dexamethasone) via π – π stacking among the aromatic rings in the graphene and the biomolecules 115,174 . Additionally, graphene derivatives increase osseointegration and osteoconductivity by stimulating cellular osteogenic differentiation, as well as bone‐like apatite production and biomineralization on the surface of implants 110,175 . One of the main factors for mimicking the properties of articular cartilage superficial and deep zones is the lubrication feature that maintains low coefficients of friction of joints.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been demonstrated that nanomaterials such as GO and rGO enhance cellular behavior over various scaffolds in order to promote and sustain tissular regeneration [133]. Fibrin, a fibrous protein, was employed as a biopolymer for the development of a nanocomposite scaffold for bone tissue engineering [134].…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Functionalized graphene and its derivates have been also used in bone regeneration and tissue engineering. Graphene can be combined with natural and synthetic biomaterials to enhance the osteogenic potential and mechanical properties of tissue engineering scaffolds [ 83 , 84 , 85 ]. Scaffolds play a central role in tissue engineering as structural support for specific cells and provide the templates to guide new tissue growth and construction [ 84 ].…”
Section: Functionalization Of Graphenementioning
confidence: 99%